Evidence-Based Assignment of Diagnostic Peritoneal Lavage (DPL) Sensitivity in Penetrating Abdominal Trauma - M. Sharifi; A. Saberi; M. Zeinalzadeh; H. Vafaei; A. Kavyani; A. Afsharfard; M . Mozaffar (Medical Journal of The Islamic Republic of Iran, 2008)
Background:There are a large number of patients with penetrating abdominal trauma who have normal vital signs and negative abdominal examination when referred to trauma centers. Agreat deal of controversy exists between authorities about screening these patients for emergency explorative laparotomy. Many references have reported more than 90% sensitivity for DPL as a diagnostic method to determine whether intraabdominal injuries were present and emergent laparotomy is indicated or not. This study is for reassignment of this sensitivity according to our own evidence. Methods: All of the patients with abdominal stab wounds and normal vital signs plus negative abdominal examination who were referred to Shohada-e-Tajrish hospital between March 2004 to December 2005, underwent local wound exploration and those confirmed to have peritoneal penetration, underwent emergency laparotomy. In the operating room and prior to surgery, under general anesthesia, DPL was performed. Then DPL results were compared with laparotomy findings and DPL sensitivity was assigned. Results: Of the total number of 34 patients, 8 had a positive DPL and positive laparotomy; 2 had a positive DPL and negative laparotomy; 8 had negative DPL and positive laparotomy, and 16 patients had negative DPL and negative laparotomy. Conclusion: According to our study, DPL sensitivity is much less than mentioned in trauma texts (approximately 50%). So, it is not a valuable tool to discriminate between operative and conservative approaches in penetrating abdominal trauma. We suggest more sensitive modalities. Laparotomy is the most sensitive approach but at the price of a high negative laparotomy rate.